Development of Russian Driverless Electric Vehicle - Andrey Mikhailovich Saykin; Sergey Evgenievich Buznikov; Denis Vladimirovich Endachev; Kirill Evgenievich Karpukhin; Alexey Stanislavovich Terenchenko (Institute of Advanced Engineering and Science, 2018)
This article overviews the history of development of driverless vehicles both in Russia and the World. Foreign experience of development of driverless vehicles, including electric traction, is analyzed. Main stages of creation of experimental NAMI driverless electric vehicle are revised. Main engineering solutions are described concerning development of advanced NAMI driverless electric vehicle, its major components and control systems. Projects aimed at environmental safety of passengers in NAMI driverless electric vehicle are exemplified. Results of bench scale and running tests of NAMI driverless electric vehicle are summarized. Major advantages of driverless energy efficient and environmentally clean transport are demonstrated.